Unpacking Academic Stress among Undergraduate Students during Thesis Writing: A Qualitative Study of Stressors, Stages, and Institutional Challenges - Luh Dewi Pusparini; I Gede Yoga Permana; Ni Wayan Surya Mahayanti (Universitas Pendidikan Ganesha, 2025)
Academic stress has become a prevalent issue among undergraduate students, particularly during the thesis writing stage, which often represents the culmination of their academic journey. The demanding nature of research tasks, coupled with institutional expectations and limited supervisory support, can significantly affect students’ psychological well-being and academic performance. This study aims to examine the factors contributing to academic stress during the thesis writing process and explore how these challenges shape students’ overall academic experience. Using a qualitative approach, data were collected through in-depth interviews with ten undergraduate students who experienced delays in completing their theses. Thematic analysis was employed to identify recuring patterns related to stress triggers and coping mechanisms. The findings reveal that time management difficulties, the complexity of research procedures, and conflicting supervisory expectations are the major sources of academic stress. Emotional exhaustion and decreased confidence were also found to hinder students’ progress. The study concludes that academic institutions should strengthen support systems by offering structured thesis guidance, clear communication channels, and time management training. These interventions can reduce stress levels and promote a healthier, more supportive environment for academic achievement.